Final answer:
To subtract the second equation from the first, you need to subtract the corresponding terms. The result is 12y = -7.
Step-by-step explanation:
To subtract the second equation from the first, we need to subtract the corresponding terms.
Starting with the x terms:
2x - 2x = 0
Next, the y terms:
7y - (-5y) = 7y + 5y = 12y
Finally, the constant terms:
-8 - (-1) = -8 + 1 = -7
Putting it all together, the result of subtracting the second equation from the first is 0 + 12y = -7, which can be simplified to 12y = -7.